The Role of Fiscal Institutions in Managing the Oil Revenue Boom. (Policy Papers; Policy Paper ;, 2007)
This paper examines the fiscal responses of oil-producing countries (OPCs) to the oil boom through 2005 and the role of special fiscal institutions (SFIs)-oil funds, fiscal rules and fiscal responsibility legislation (FRL), and budgetary oil prices-in fiscal management in OPCs, and draws some general lessons.